Preparation of Single-Phase Films of CH3NH3Pb(I1–x Br x )3 with Sharp Optical Band Edges - Sadhanala, Aditya; Deschler, Felix; Thomas, Tudor H; Dutton, Siân E; Goedel, Karl C; Hanusch, Fabian C; Lai, May L; Steiner, Ullrich; Bein, Thomas; Docampo, Pablo; Cahen, David; Friend, Richard H (The journal of physical chemistry letters, 2014)
Organometallic lead-halide perovskite-based solar cells now approach 18% efficiency. Introducing a mixture of bromide and iodide in the halide composition allows tuning of the optical bandgap. We prepare mixed bromide–iodide lead perovskite films CH3NH3Pb(I1–x Br x )3 (0 ≤ x ≤ 1) by spin-coating from solution and obtain films with monotonically varying bandgaps across the full composition range. Photothermal deflection spectroscopy, photoluminescence, and X-ray diffraction show that following suitable fabrication protocols these mixed lead-halide perovskite films form a single phase. The optical absorption edge of the pure triiodide and tribromide perovskites is sharp with Urbach energies of 15 and 23 meV, respectively, and reaches a maximum of 90 meV for CH3NH3PbI1.2Br1.8. We demonstrate a bromide–iodide lead perovskite film (CH3NH3PbI1.2Br1.8) with an optical bandgap of 1.94 eV, which is optimal for tandem cells of these materials with crystalline silicon devices.